2021
DOI: 10.1016/j.sjbs.2021.02.046
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ecological and edaphic factors on biodiversity of soil nematodes

Abstract: Nematodes are the most diverse and highly significant group of soil-inhabiting microorganisms that play a vital role in organic material decomposition and nutrient recycling. Diverse geographical locations and environmental gradients show a significant impact on the diversity of nematodes. Present study aims to assess the effects of ecological (altitude, temperature, moisture) and edaphic (soil pH, nutrients, soil patches) factors on the soil nematode diversity and structure at five different landsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 67 publications
4
40
2
Order By: Relevance
“…This is consistent with the common paradigm in ecology that an increase in temperature promotes biological activity rates of species, in turn facilitating the interaction between the species (Yuan et al, 2021 ). (3) Climatic variables have a more important effect in determining nematode communities compared to edaphic variables in term of community diversity, community structure and community co‐occurrences, since along elevation gradients climates usually become more distinctive than soil characteristics (Nisa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the common paradigm in ecology that an increase in temperature promotes biological activity rates of species, in turn facilitating the interaction between the species (Yuan et al, 2021 ). (3) Climatic variables have a more important effect in determining nematode communities compared to edaphic variables in term of community diversity, community structure and community co‐occurrences, since along elevation gradients climates usually become more distinctive than soil characteristics (Nisa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Matute et al (2012) also reported that the abundance of nematodes associated with Brassica rapa (fungivores, bacterivorous, predatory, and plant-parasitic) was negatively correlated to soil pH. Soils with acidic pH increase nematode reproduction and enhance soil microbes (Nisa et al 2021). In conclusion, nematodes belonging to eight genera were identified in the Ngantang sub-district and six genera in the Jatikerto Agrotechnopark and UB Forest.…”
Section: Nematode Diversity and Abundance In Coffee Plantations In Malang Districtmentioning
confidence: 85%
“…In addition, predatory nematodes play an important role in nematode communities, acting as agents of biological control and bio-indicators of ecological change (Cock et al 2012). Ecological factors, such as altitude, plant diversity, precipitation, and temperature, affect nematode distribution, diversity, and abundance (Nisa et al 2021). Soil abiotic factors, including temperature, pH, waterholding capacity, and mineral composition, also influence nematode abundance and communities (Sholeha et al 2017;Van Den Hoogen et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These differences may be due to geographical, weather and edaphic disparities, among other possible factors. As opined by numerous authors, the prevalence and average densities of nematode genera vary with ecological variations [22,23,24,25,26,27] . Using community analyses and based on the prominence values, the study has also showed that Meloidogyne sp.…”
Section: Discussionmentioning
confidence: 97%